Estimating the historical distribution, abundance and ecological contribution of Modiolus modiolus in Strangford Lough, Northern Ireland - Strong, James Asa; Moore, Heather; Service, Matthew (Biology and Environment: Proceedings of the Royal Irish Academy, 2016)
Strangford Lough is a large sheltered marine inlet in Northern Ireland. It is also a designated Special Area of Conservation based partially on the presence of an extensive area of Modiolus modiolus (Linnaeus, 1758) biogenic reef. However, this feature is believed to have declined substantially over the last 40 years. The objective of the study was to estimate the size of this decline both in terms of extent and abundance. This study combined (i) new survey data (a dedicated multibeam echo-sounder survey of the Lough), (ii) a habitat suitability model for M. modiolus with (iii) historical diver surveys to estimate the extent and abundance before 1985 (before the suspected period of greatest decline), 2003 (during the introduction of a ban on mobile fishing gear in the Lough) and 2007 (the most recent diver survey available). Estimations indicate that the extent reduced from approximately 12.6km2 in 1986 to just 5.7km2 by 2007 and the abundance declined by 87% in the same period. The decline has implications both for the remaining population of M. modiolus and ecosystem functionality within the Lough, which are both discussed in detail.